Driving factors of the potentially toxic and harmful species of Prorocentrum Ehrenberg in a semi-enclosed Mediterranean lagoon (Tunisia, SW Mediterranean) - SAHRAOUI, I.; BOUCHOUICHA, D.; HADJ MABROUK, H.; SAKKA HLAILI, A. (Mediterranean Marine Science, 2013)
We analysed the dynamics of the potentially toxic and harmful species of Prorocentrum Ehrenberg in Bizerte lagoon (important aquaculture area, Northern Tunisia), substantiating the possible driving forces (temperature, salinity and nutrients), based on a two years database. We revealed that Prorocentrum spp. blooms of high magnitude (104 - 105 cells l-1) occurred mostly during the period of late winter to early spring. We found five species of Prorocentrum, two of which, P. lima and P. cordatum, the most common during the field, are confirmed agents of Diarrhetic Shellfish Poisoning in various regions of the world ocean. Prorocentrum sp., P. micans, and P. gracile were however present only sporadically but with high cell abundances, exemplifying bloom densities. Canonical correspondence analysis revealed that P. minimum and P. lima were much more abundant in eutrophied waters characterized here by high Chl a biomass, while P. gracile species occurred principally in warm waters. Furthermore, Prorocentrum sp. and P. micans seemed more likely to proliferate in saline waters with high concentrations of inorganic nutrients (nitrate, ammonia and phosphate). Our study calls attention to a possible intensification of DSP events in the Bizerte lagoon, given the propensity of Prorocentrum spp. to proliferate in a eutrophied system.